PENGGUNAAN METANOL SISA REAKSI SEBAGAI REAKTAN PADA PROSES TRANSESTERIFIKASI MINYAK KELAPA SAWIT MENJADI BIODIESEL - Elvianto Dwi Daryono; Febriara Fassa Aulia Rahman; Zukhriyah Zukhriyah (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
In the process of making biodiesel with a transesterification reaction, an effective, efficient and inexpensive raw material is palm oil because of its abundant availability. In the transesterification process, the addition of methanol is deliberately exaggerated so that the reaction shifts towards the product and the reaction is more perfect and the excess methanol reagents in the process can be reused as reactants. This research was conducted to obtain optimal levels and yield of methyl esters by utilizing the residual methanol reaction. The transesterification process is carried out at 65°C, the molar ratio of palm oil: methanol is 1: 6, the mass of NaOH catalyst is 1% oil mass and the stirring speed is 150 rpm. The residual methanol from the transesterification reaction is used as a reactant in the subsequent transesterification reaction by varying the mass of the remaining methanol addition of the reaction which is 5%, 10% and 15% of the mass of the initial methanol and also varying the reaction time of 15, 30, 45, 60 and 75 minutes. From the results of the research, it was obtained the optimum conditions for the addition of 5% residual reaction methanol and 60 minutes reaction time, get a yield of 90.60% and a concentration of methyl ester 97.69% (meet SNI 7182: 2015). Methyl ester products at the optimum process conditions also meet SNI 7182: 2015 for densities of 0.85 gr / ml and acid valuesof0.42mg-KOH/gr.